PENGARUH EDUKASI KESEHATAN TENTANG PERILAKU BUANG AIR KECIL TERHADAP PENCEGAHAN INFEKSI SALURAN KEMIH DI SEKOLAH SMPN 37 MEDAN - Dina Sri M. Simarmata; Harsudianto Silaen (Universitas Murni Teguh, 2026)
Urinary tract infections occur when microorganisms such as bacteria, fungi, or viruses invade parts of the urinary system. The primary bacterium that causes infection is Escherichia coli. The objective of this study is to determine the effect of health education regarding urination behavior on the prevention of urinary tract infections. This study used a quantitative method with an experimental approach employing a One Group Pretest–Posttest Design by comparing pre-test and post-test data. The population consisted of all 180 students of grade IX, and the sample was obtained using a total sampling technique; however, the number of respondents who were present during data collection was 154 students. The findings showed an increase in students’ knowledge, attitudes, and behaviors related to urinary tract infection prevention after the health education intervention was provided. The Wilcoxon test revealed a p-value < 0,05 for all variables, indicating that health education had a significant effect on improving students’ knowledge, attitudes, and urination behavior in preventing urinary tract infections. It is concluded that health education is effective in improving students’ understanding and behavior regarding the prevention of urinary tract infections. This study is expected to serve as a reference for schools, health workers, and future researchers in implementing continuous health education programs.